Dietary administration effects of exopolysaccharide from potential probiotic strains on immune and antioxidant status and nutritional value of European sea bass (Dicentrarchus labrax L.). (August 2020) - Mahdhi, Abdelkarim; Chakroun, Ibtissem; Espinosa-Ruiz, Cristóbal; Messina, Concetta Maria; Arena, Rosaria; Majdoub, Hatem; Santulli, Andrea; Mzoughi, Ridha; Esteban, Maria Angeles
Abstract: The use of biological immunostimulants is considered a valuable practice to improve culture conditions in aquaculture sector that may help to increase production and maintain healthy environment. We undertook this study in order to evaluate the potential effect of the administration of two exopolysaccharides (EPS) "EPLB" and "EPB" derived from potential probiotic strains on immune and antioxidant status of European sea bass ( Dicentrarchus labrax L.) larvae. In order to find out if the EPSs have an effect on the biochemical composition during the trial period, the nutritional value has been evaluated. The results revealed that expression levels of immune-relevant genes ( infg, Il1b, Il8, Il6 and tcr-β) in the gut and head kidney and the scavenging enzymes ( cat, sod, gr ) genes in the liver were modulated. In fact, the dietary supplementation with the tested EPSs, significantly enhances the expression of immune-associated genes in the head-kidney, particularly infg and tcrβ, as well as catalase gene in liver. During the period of study, EPSs administration did not affect the fatty acid profiles of larvae, which is balanced. This is confirmed by the Docosahexaenoic acid / Eicosapentaenoic acid ratio and demonstrates that EPLB and EPB can be administrated without any negative effect on biochemical composition of European sea bass. The present findings provided evidence that the tested EPSs with antibacterial and antioxidant activities can enhance immune response without negative effect on the biochemical composition. The used EPSs can be considered as a good source of natural functional aquafeed ingredients for European sea bass. Graphical abstract: Unlabelled Image Highlights: Bacterial exopolysaccharide (EPS) as anti-bacterial, anti-biofilm and anti-oxidant agent EPS didn't affect nutritional value, and modulate immune and antioxidant status. EPS can improve culture conditions and maintain healthy environment.